FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PADA IBU PRIMIGRAVIDA DALAM MENGHADAPI PERSALINAN DI WILAYAH KERJA PUSKESMAS BOJONGGAMBIR - Mira Mirnawati; Zesika Intan Navelia; Siti Fadhilah (PT. Saha Kreasi Indonesia, 2025)
Background: Anxiety can be experienced by pregnant women when facing labor. Anxiety may be influenced by factors such as age, education, and occupation of the pregnant women. Preliminary study through interviews with a midwife working at Bojonggambir Health Center found that primigravida women in their third trimester experienced anxiety. Objective: To determine the relationship between the characteristics of primigravida women and their level of anxiety in facing the labor process in the working area of Bojonggambir Health Center, Tasikmalaya Regency. Methods: This study used a descriptive research design. The population in this study included all primigravida women in their third trimester within the working area of Bojonggambir Health Center. The sampling technique used was total population sampling, consisting of 30 primigravida women in their third trimester. Results: The results of the study showed a significant relationship between maternal characteristics based on age of primigravida women and their level of anxiety (p = 0.003 < 0.05). There was also a significant relationship between education level of primigravida women and their level of anxiety (p = 0.009 > 0.05), as well as a significant relationship between occupation of primigravida women and their level of anxiety (Chi-Square = 0.002 and Fisher’s Exact Test p = 0.004 < 0.05). Conclusion: Although the majority of primigravida women in their third trimester in the working area of Bojonggambir Health Center did not experience severe anxiety, some still experienced anxiety when facing the labor process. Therefore, further efforts are needed to provide education that not only increases knowledge but also fosters positive attitudes and encourages pregnant women’s readiness in facing labor.